Opening up unseen migration narratives in Finnish education : three Russian-speaking success stories - Platonova, Zhanna (2020)
When a person changes the country of living, a new story about oneself begins. The plot is informed by its characters and setting— migrants, their families, and the surrounding community. According to the existing literature, acculturation is a long-lasting complicated process that depends on the interplay of various circumstances in a person's life (Sam & Berry, 2010). The object of the study was to explore the successful acculturation journey of three Russian-speaking educators working in the Finnish educational system. Using narrative inquiry, this study unfolds the participants' stories creating a layered narrative that encompasses many aspects of identity that intertwined to form a unique experience. To uncover the meaning-making of being a successful Russian-speaking migrant in Finland, in-depth interviews with three participants were conducted. The study sееks tо роrtrait depth and subtlеty in dеsсriрtiоns of the раrticipаnts. The imаgеs оf the раrticipаnts рrеsеnt а mоrе соmрlеx picturе thаn thоsе fоund in studiеs that examine migrants based upon only one or two traits, to the exclusion of others. Narrative content was analyzed, using a combination of deductive and inductive approaches. Five themes emerged from this study. First, a strong professional identity significantly improved the participants’ actions for integration into Finnish education. Second, the participants’ past life experiences served as a supporting structure for life after migration. Third, their ability to be effective learners facilitated the planning and implementation of goal-oriented activities as well as Finnish language learning. Fourth, the participants recognized luck in various manifestations as a fairly influential aspect in achieving goals and making the right choices and decisions, which helped a smoother acculturation process. Fifth, the cultural influence of the families on the participants’ attitudes to Finnish and Russian cultures were powerful; they resulted in such a way that each participant’s mindset was formed in a sophisticated way, like a unique patchwork of elements from a variety of cultures, collected under the umbrella of education completed in Russia and supplemented in other countries.